2010
DOI: 10.1037/a0019247
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing treatment outcome of patients at risk of treatment failure: Meta-analytic and mega-analytic review of a psychotherapy quality assurance system.

Abstract: The current state of evidence appears to support the efficacy and effectiveness of feedback interventions in enhancing treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
478
3
25

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 582 publications
(523 citation statements)
references
References 43 publications
17
478
3
25
Order By: Relevance
“…A meta-analysis of six studies comprising over 6000 treatments (Shimokawa, Lambert, & Smart, 2010) found that regularly assessing and reviewing patient treatment progress feedback with the OQ patient feedback system (e.g. Lambert, 2015) resulted in improved outcomes for patients demonstrating difficulties in making or sustaining treatment gains.…”
Section: Development Of the Pitq-p And Pitq-tmentioning
confidence: 99%
“…A meta-analysis of six studies comprising over 6000 treatments (Shimokawa, Lambert, & Smart, 2010) found that regularly assessing and reviewing patient treatment progress feedback with the OQ patient feedback system (e.g. Lambert, 2015) resulted in improved outcomes for patients demonstrating difficulties in making or sustaining treatment gains.…”
Section: Development Of the Pitq-p And Pitq-tmentioning
confidence: 99%
“…Moreover, this conclusion has not changed in recent years. There has been no "explosion" of new research findings that leads us to believe that this approach will provide probably better as a result (Tam Huiyi and Ronan, in press;Bickman et al 2011;Shimokawa et al 2010). We hasten to point out that both alliance research and feedback research have been subject to a variety of methodological challenges, especially in real-world settings, and there is some debate as to the true effect size of mediators such as alliance or feedback.…”
Section: Is There a Future For Therapists?mentioning
confidence: 99%
“…De même, les psychologues étaient aussi plus en faveur du suivi des résultats (outcome) du traitement en utilisant des mesures validées. Ceci revêt une importance particulière puisque le suivi en continu des résultats peut améliorer l'efficacité d'un traitement (Lambert & Shimokawa, 2011 ;Overington & Ionita, 2012 ;Shimokawa, Lambert & Smart, 2010). Or, ici encore, il est possible que ceci soit lié à la présence d'un nombre plus élevé de détenteurs de doctorat chez les psychologues, une étude récente ayant démontré que les docteurs en psychologie avaient une plus grande expertise que les maîtres en psychologie en matière de suivi en continu et d'évaluation de l'issue thérapeutique (Ionita & Fitzpatrick, 2014).…”
Section: La Pratique Fondée Sur Des Données Probantes Et Le Suivi Desunclassified